2011
DOI: 10.1007/s10750-011-0961-4
|View full text |Cite
|
Sign up to set email alerts
|

Some evidence for different ecological pressures that constrain male and female body size

Abstract: The dwarf morph of the Lake Tanganyika cichlid Telmatochromis temporalis uses empty snail shells as shelters and breeding sites in shell beds, in which many empty shells exist. Here, we assessed selection forces regulating body size in this fish. Field observations showed that large males tended to have a greater number of females in their territories, suggesting that sexual selection favours large males. Nonetheless, a transplant experiment suggested that male body size was limited by the ability to hide in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 50 publications
(61 reference statements)
1
35
0
Order By: Relevance
“…However, they could alternatively be an innate behaviour linked to requirements for optimal habitat, and specifically the requirements for self-protection, egg laying and brood care 38 . Small females may be unable to defend shelter on rock habitat because of competition from large growing females, but they may be favoured on shell habitat as they can escape predators and lay eggs deep enough in shells to avoid the numerous egg predators, including freshwater crabs 26 . Similarly, large growing females would be the most successful competitors on rock habitat, and would be favoured by fecundity selection on rock given their higher reproductive potential 26 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, they could alternatively be an innate behaviour linked to requirements for optimal habitat, and specifically the requirements for self-protection, egg laying and brood care 38 . Small females may be unable to defend shelter on rock habitat because of competition from large growing females, but they may be favoured on shell habitat as they can escape predators and lay eggs deep enough in shells to avoid the numerous egg predators, including freshwater crabs 26 . Similarly, large growing females would be the most successful competitors on rock habitat, and would be favoured by fecundity selection on rock given their higher reproductive potential 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Small females may be unable to defend shelter on rock habitat because of competition from large growing females, but they may be favoured on shell habitat as they can escape predators and lay eggs deep enough in shells to avoid the numerous egg predators, including freshwater crabs 26 . Similarly, large growing females would be the most successful competitors on rock habitat, and would be favoured by fecundity selection on rock given their higher reproductive potential 26 . However, establishment of mature rock ecomorph females on shell habitat is also likely to be prevented because of the high potential for predation of both adult fish and eggs laid close to shell entrances 26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this species substrate use of individuals appears strongly linked to the availability of shelter and predation threat. Adults of both ecomorphs are believed to be highly vulnerable to multiple predators that characterise hard substrate environments of Lake Tanganyika (Takahashi et al 2012), including piscivorous fish (catfishes, mormyrids, cichlids, mastacembelid eels), birds (kingfishers and cormorants), mammals (spotted-neck otters) and reptiles (water cobra) (Konings 1998). It has been found that body size matches available shelter size in T. temporalis, and that in transplant experiments rock ecomorphs are unable to make use of empty shells as shelter against predators (Takahashi et al 2012).…”
Section: Major Drivers Of Population Genetic Structuringmentioning
confidence: 99%